Meeting the challenges of COVID-19: How and to what extent did organizational communicators prepare, respond and learn from the pandemic - Summers, Elizabeth (My University, 2023)
The COVID-19 pandemic created one of the most significant crises our modern society has faced. Organizational communicators play a vital role in responding to and recovering from crisis. In fact, an organization’s ability to recover from crisis depends on how quickly it can establish strong lines of communication with its stakeholders – a task well suited to the strategic value communicators bring to their organizations. This capstone research study examined the viewpoints of 71 survey respondents and 11 in-depth interview participants, analyzing how the COVID-19 pandemic impacted crisis preparedness and management, and the role organizational communicators played within crisis management before, during and after the pandemic. While findings show that communicators demonstrated excellence in public relations through the COVID-19 crisis, there is still additional work required to embed learnings from the pandemic in future crisis preparedness plans. This research can contribute to future studies on how organizational communicators contribute to crisis preparedness and management and how leadership can better prepare their organizations for crisis. Findings provide insights for organizational communicators on how to participate in crisis preparedness and management more actively. This study may help to inform organizational crisis communications response, and best practices in crisis preparedness and management.
Keywords: crisis management; crisis preparedness; crisis communication; crisis response; crisis learning; COVID-19 pandemic; excellence in public relations